Attentional capture: An ameliorable side-effect of searching for salient targets - Liesefeld, Heinrich R.; Liesefeld, Anna M.; Müller, Hermann J. (Visual cognition, 2021)
This commentary highlights that some of the remaining discrepancies in the attentional-capture debate can be resolved by a simple assumption: observers do not use the priority map when this map is useless to solve the task. Rather, whenever search targets are known to be non-salient, observers resort to a previously postulated alternative search strategy for which (distractor) saliency signals are irrelevant. Equipped with this assumption, we trace thus-far unaccounted-for discrepancies between empirical studies on attentional capture back to specific design choices that affect relative target saliency (display density and non-target heterogeneity).